(untitled) (International Seven Journal of Multidisciplinary, 2023)
The Family Guidance Service, which is the subject of this article, is one of the places where the Professional Internship activity of the School of Social Work is carried out. It is linked to the University of the Elderly, a University Extension Program of the Federal University of Pará, and its objective is the intervention of Social Work in the area of human aging. It should be noted that, during the course of the activities, it was proven that the professional practice developed with the elderly people served was in line with the profession’s normative documents, which together underpin the Ethical-Political Project of Social Work.